2015
DOI: 10.1002/cbic.201500482
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acylethanolamines Bind to SIRT6

Abstract: Sirtuin 6 (SIRT6) is an NAD+-dependent histone deacetylase enzyme that is involved in multiple molecular pathways related to aging. Initially, it was reported that SIRT6 selectively deacetylated H3K9Ac and H3K56Ac, however, more recently it has been shown to preferentially hydrolyze long-chain fatty acyl groups over acetyl groups in vitro. Subsequently, fatty acids were demonstrated to increase the catalytic activity of SIRT6. In this study we investigated whether a series of N-acylethanolamines (NAEs), querce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 28 publications
2
41
1
Order By: Relevance
“…The inhibitory activity of resveratrol towards SIRT1 remains controversial, and we can at least say that resveratrol did not greatly affect SIRT activity in our assay system. Quercetin had similar effects on SIRT1 and SIRT6 activities: that is, inhibition at lower concentration, but activation at higher concentration, in accordance with a previous report (Figure D) . Taken together, these results suggest that SIRT modulators generally have similar effects on deacetylase activity and deacylase activity towards long‐chain fatty acyl groups.…”
Section: Resultssupporting
confidence: 92%
“…The inhibitory activity of resveratrol towards SIRT1 remains controversial, and we can at least say that resveratrol did not greatly affect SIRT activity in our assay system. Quercetin had similar effects on SIRT1 and SIRT6 activities: that is, inhibition at lower concentration, but activation at higher concentration, in accordance with a previous report (Figure D) . Taken together, these results suggest that SIRT modulators generally have similar effects on deacetylase activity and deacylase activity towards long‐chain fatty acyl groups.…”
Section: Resultssupporting
confidence: 92%
“…Phenolic compounds, such as quercetin and luteolin, also enhance SIRT6 deacetylation activity, albeit at very high concentrations [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that NAEs could activate sirtuin 6 in vitro , a NAD + ‐dependent histone deacetylase, which is involved in regulating genomic stability, oxidative stress and glucose metabolism (Rahnasto‐Rilla et al, ). It is at present not known whether this has any physiological or pharmacological significance.…”
Section: Formation and Targets Of N‐acylethanolaminesmentioning
confidence: 99%